PERSEPSI MAHASISWA FIB UNDIP TERHADAP ELECTRONIC LIBRARY UPT PERPUSTAKAAN UNIVERSITAS DIPONEGORO - Ati, Sri; Rohmiyati, Yuli; Danny, Desy Ery; Taufik, Amin; yanto, Heri (HUMANIKA, 2013)
ABSTRACT Electronic Library or often called E-Library growth rapidly and many of libraries in Indonesia applied this concept. Library of Diponegoro University has been operating E-library since 2005, and have made many changes, in term of its appearance, or information shown in the web. This E-Library is used by the university to contribute the implementation of e-learning and e-research at Diponegoro University. This research is aimed at knowing the students perception of UNDIP’s E-Library’s service. The methods used in this research descripve quantitative-qualitative types, using questionaire dan interview data collection. The benefit of this research can hopefully improve Diponegoro University Library services, especially at E-Library service. The results of this study are most of the students feel satisfy with the services given by the librarian concerning the convenience of web accessibility, the rapidity web access, contents of the web, types and kinds of information provided by the Diponegoro University’s website. Meanwhile for frequency of web visitation most of the respondents are rare visiting the we. They said that it is caused by the collections are not up to date and the appearances are not interesting. For the librarians they said most of them are not friendly and hospitable. The student hope library should improve their service to meet their users needs. Keywords: Users’ perception; Electronic Library, Library of Diponegoro University